ABC transporters in drug-resistant epilepsy: mechanisms of upregulation and therapeutic approaches. (June 2019) - Leandro, Kevin; Bicker, Joana; Alves, Gilberto; Falcão, Amílcar; Fortuna, Ana
Graphical abstract: Abstract: Drug-resistant epilepsy (DRE) affects approximately one third of epileptic patients. Among various theories that try to explain multidrug resistance, the transporter hypothesis is the most extensively studied. Accordingly, the overexpression of efflux transporters in the blood-brain barrier (BBB), mainly from the ATP binding cassette (ABC) superfamily, may be responsible for hampering the access of antiepileptic drugs into the brain. P-glycoprotein and other efflux transporters are known to be upregulated in endothelial cells, astrocytes and neurons of the neurovascular unit, a functional barrier critically involved in the brain penetration of drugs. Inflammation and oxidative stress involved in the pathophysiology of epilepsy together with uncontrolled recurrent seizures, drug-associated induction and genetic polymorphisms are among the possible causes of ABC transporters overexpression in DRE. The aforementioned pathological mechanisms will be herein discussed together with the multiple strategies to overcome the activity of efflux transporters in the BBB – from direct transporters inhibition to down-regulation of gene expression resorting to RNA interference (RNAi), or by targeting key modulators of inflammation and seizure-mediated signalling.